Becoming a teacher - Parkay, Forrest W. (Boston, MA Pearson Education, Inc., 2020)
"The 11th edition of Becoming a Teacher continues to listen to the voices of those who care deeply about teaching--professionals and expert teachers, beginning teachers just learning the ropes, students in America's class-rooms, and teacher education students deciding if teaching is their best career path--to help readers discover the answer to the question, "Is teaching for me?" With the help of these stakeholders, the 11th edition focuses on teacher quality and provides in-depth cover-age of critical issues such as the following: - Every Student Succeeds Act (ESSA) - diversity and culturally competent teaching - social justice and democracy - students of undocumented immigrant parents - teacher leadership, political activism, and change facilitation - Adverse Childhood Experiences (ACE) and trauma-sensitive schools - federal education agenda Becoming a Teacher embraces and articulates the changing field of education, outlining ways to be an agent of change in the profession, pinpointing meaningful uses of technology in education, clarifying realities of diversity in the classroom, and clearly outlining past, present, and future thoughts on curriculum, instruction, assessment, management, philosophy, and issues in education. This down-to-earth and straightforward approach provides students with the tools and information necessary to answer the questions, "What does it take to become a high-quality teacher?" and "Do I want to teach?""--
Teaching: your chosen profession -- Today's teachers -- Today's schools -- Philosophical foundations of U.S. education -- Historical foundations of U.S. education -- Governance and finance of U.S. schools -- Ethical and legal issues in U.S. education -- Today's students -- Addressing learners' individual needs -- Creating a community of learners -- Curriculum, standards, assessment, and student learning -- Integrating technology into teaching -- Becoming a professional teacher.
Includes bibliographical references and indexes.
Keywords: Teaching -- Vocational guidance; Education -- Study and teaching -- United States